NMR investigation of boron impurities in refined metallurgical grade silicon. Issue 9 (27th April 2015) - Grafe, Hans‐Joachim; Löser, Wolfgang; Schmitz, Steffen; Sakaliyska, Miroslava; Wurmehl, Sabine; Eisert, Stefan; Reichenbach, Birk; Acker, Jörg; Rietig, Anja; Ducke, Jana; Müller, Tim
Abstract : The nuclear magnetic resonance (NMR) method was applied for tracking boron impurities in the refining process of metallurgical grade (MG) silicon. From the NMR signal of the 11 B isotope at an operating temperature 4.2 K, the boron concentration can be estimated down to the order of 1–10 wppm B. After melting and resolidification of MG‐Si alloyed with Ca and Ti, a major fraction of B impurities remains in the Si solid solution as inferred from the characteristic NMR frequency. The alloying element Ti does not form substantial fractions of TiB2 . Acid leaching of crushed powders of MG‐Si alloyed with Ca and Ti can diminish the initial impurity content of B suggesting its accumulation in the grain boundary phases. NMR signals of TiB2 at 4.2 K and room temperature (RT), and of poly‐Si with different B doping at 4.2 K.